Some hormonal systems in males with arterial hypertension and metabolic syndrome - A. N. Britov; A. M. Inarokova; M. A. Umetov (Кардиоваскулярная терапия и профилактика)
Aim. To study carbohydrate, hormonal, and lipid parameters in patients with mild to moderate arterial hypertension (AH) and metabolic syndrome (MS) components. Material and methods. In total, 265 males (mean age 53.4±4.2 years) with mild to moderate AH and MS components were examined. Comparison group included 27 males with excess body mass (BM) without AH and carbohydrate metabolism disturbances, control group – 20 healthy males with normal BM. All participants underwent office blood pressure (BP) measurement, anthropometry, glucose tolerance test; lipid profile, levels of fasting and postglucose load insulin, leptin, thyroid hormones, cortisol, thyrotropic (TTH) and adrenocorticotropic hormone (ACTH) were measured. Results. Basal hyperinsulinemia was observed in 59% patients with isolated AH, and 52% of normotensive males with excess BM. In 93% of normotensive males with excess BM, hyperleptinemia was registered; insulin resistance (IR) was observed only in 52%. In AH and MS men, subclinical hypothyrosis (76%), increased levels of insulin, leptin, ACTH and cortisol were observed more often than in men with isolated AH or healthy participants. In obese individuals, there was a positive correlation of leptin level with BM, TTH, ACTH, cortisol, insulin, and triglycerides. Conclusion. In patients with AH and MS, increased cortisol, ACTH, insulin, and leptin production was linked to obesity severity, and was associated with subclinical hypothyrosis. In its turn, chronic increase in cortisol and insulin levels could facilitate IR and fat tissue percentage increase.